The Effectiveness of Creative Problem-Solving Learning Model in Mathematics Learning - Yuliana, Riza; Utomo, Dwi Priyo; Ismail, Agung Deddiliawan (MEJ (Mathematics Education Journal), 2019)
This research aimed at assessing the effectiveness of the creative problem-solving learning model in 8th grade of mathematics learning. The assessment of the effectiveness of learning model was reviewed based on three aspects, namely students’ activities, students’ responses to the learning model, and students’ learning outcomes. The type and approach, which used in this research, were quantitative descriptive with the research subjects of 8th-C class; moreover, the subjects consisted of 32 students. The instruments used to assess the effectiveness of the learning model were the students’ activity observation sheet, students’ responses questionnaire, and test sheet. The results of the research showed that the students’ activities were categorized as very good, in which the percentages were 84.38%. The students’ responses were categorized as very good with a percentage of 82.53%. The students’ learning outcomes in a classical manner could be said as complete with the completeness of 71.88%. Therefore, it can be concluded that the implementation of creative problem-solving learning model in mathematics learning can be said as effective.